Development of documentary films in the Tatar autonomous Soviet Socialist Republic - Galimzyanova, Alina Tagirovna (Opción, 1970)
The aim of the article is to explore the process of the documentary film production's formation and to determine the main directions of its development in one of the national republics of the USSR, namely the Tatar Autonomous Soviet Socialist Republic, since the pre-Soviet period of cinema. The problem-chronological approach is the leading one in this research. In result, by the end of the 1980s, the sharply worsening situation in the country in all spheres of life affected public institutions. In conclusion, a distinctive feature of this work is an integrated approach to the study of the TASSR cinematography history.